Comparison of Corneal Wave Speed and Ocular Rigidity in Normal and Glaucomatous Eyes. Issue 10 (October 2021) - Kazemi, Arash; Zhou, Boran; Zhang, Xiaoming; Sit, Arthur J.
Abstract : Precis: Ocular biomechanics were compared between treated glaucoma patients and healthy subjects matched for age, intraocular pressure (IOP), and axial length. There was no difference in corneal wave propagation speed, but ocular rigidity was lower in glaucomatous eyes. Purpose: Ocular biomechanical properties are important in understanding glaucoma pathogenesis but the affected tissues are unclear. In this study, we compared corneal wave speed (a measure of corneal elasticity) and ocular rigidity coefficient between glaucomatous and normal eyes. Materials and Methods: Twenty glaucomatous eyes from 10 patients and 20 normal eyes from 13 controls, matched for age, IOP, and axial length were included. Ocular rigidity was calculated based on the difference in supine IOP by pneumatonometry with and without a 10-g weight. Corneal wave speed was determined by ultrasound surface wave elastography. A small, 0.1-second harmonic vibration at 100 Hz was generated through the closed eyelids. Wave propagation was captured by an ultrasound transducer, and wave speed was determined from the phase change with distance. Comparisons were performed using generalized estimating equation models. Results: There were no significant differences in corneal wave speed between glaucomatous and normal eyes (2.16±0.25 vs. 2.07±0.16 m/s, P =0.17). However, ocular rigidity was significantly lower in glaucomatous eyes (0.0218±0.0033 vs. 0.0252±0.0050/μL, P =0.01). Corneal wave speed was not correlated with age and IOP in either group ( P ≥0.23) but was correlated with ocular rigidity ( R =0.48, P =0.02) and inversely correlated with axial length ( R =−0.53, P =0.01) in glaucomatous eyes. Conclusion: Glaucomatous eyes tend to have lower ocular rigidity than healthy eyes with similar age, IOP, and axial length. However, the lack of a difference in corneal wave speed suggests that corneal tissue may not be significantly affected, and scleral changes likely play a more important role in glaucoma.